An analysis of relaparotomy in operative obstetrics - Kumari, Archana; Vidyarthi, Anubha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Relaparotomy in obstetrics following caesarean section or laparotomy is associated with high morbidity and mortality and hence, considered as maternal near miss. Selection of patient for the same is crucial. This study was done to know the incidence, indications, the risk factors, intraoperative procedures and mortality rates of relaparotomy. Methods: A retrospective analysis of relaparotomy after primary obstetric surgery over a period of two and half years (June 2016 to November 2018) was done in department of obstetrics and gynecology of Rajendra Institute of Medical Sciences, Ranchi, India. Results: During study period 28 cases of relaparotomy (18 inhouse and 10 referred cases) were identified. The incidence of relaparotomy was 0.24%. Intraperitoneal hemorrhage (39.2%) was commonest indication of reoperations followed by PPH (17.8%), rectus sheath hematoma (14.8%) and burst abdomen (10.7%). Obstructed labor (32.1%) was commonest indication of primary cesarean. Hysterectomy was required in 8 cases (25.7%), evacuation of blood for hemoperitoneum was required in another 8 cases. Most cases of hemorrhage were reopened within 24 hours, whereas most case of the rectus sheath hematoma, burst abdomen, and broad ligament hematoma were reopened between 5-9 days. Conclusions: Relaparotomy is often a lifesaving procedure. Decision to perform and manage relaparotomy should always be done by senior obstetricians. Meticulous surgical techniques to secure hemostasis at time of primary surgery should be adopted. Strict postoperative vigilance, is of utmost importance for early detection of intraperitoneal hemorrhage and other complications requiring relaparotomy as timely intervention.